Estimation of the Impact of the Age Difference in Households of the Same Generation on the Age Level of Consumption - K. V. Kuznetsov (Статистика и экономика)
The available methods for calculating the age level of consumption focus on determining the level of consumption by children. At the same time, previous studies show a decrease in the level of consumption after retirement. From a research point of view, it is of practical interest to estimate the distortion of one-year age profile of consumption depending on the age difference between the adult members of the household. Among common episodic households, the paper compares the age profiles of consumption for households with two adults aged 18 to 80 years. The paper compares indexes of average per capita consumption, and estimates the level of age difference in households for the age level of consumption. The author introduces such a concept as “net consumption”, under the influence of which sensitivity to age is absorbed. To create “net consumption” in the general chronology, only households with a minimum age difference are examined.The purpose of the study. Estimation of the age level of consumption depending on the demographic characteristics of the household is little studied in modern literature. As a rule, the papers provide methods for assessing the level of children consumption. However, when creating age profiles of consumption, the age characteristics of households are not taken into account. The aim of the study is to assess the impact of the difference in the age of people living together in a household on the age profiles of consumption. Both in Russia and in the EU countries, the average difference in age between the first marriage is on average 2.5 years, and the largest difference can reach more than 30 years. From a statistical point of view, it is of practical interest to study the average per capita age level of consumption depending on the difference in the age of a married couple.Materials and methods. The source of data for the study is the Household Budget Survey (HBS) conducted by Rosstat for 2020. The paper compares age profiles of consumption created by the minimum age of the household, by the maximum, by the average, and by the classical method. In addition, the paper compares the age profiles created by the classical method, taking into account the limitation of the age difference between household members.Results. The results obtained from the 2020 HBS survey allow conclusions to be drawn about different age profiles depending on the proposed calculation methods. The results of the study showed that among households consisting of two people, almost a third of households (34.1%) have an age difference of more than 5 years. In the context of calculating one-year age profiles of consumption, a significant age difference in age will lead to a distortion of age profiles of consumption. Among households consisting of two people, the largest difference in the level of average per capita consumption between all households of two people and households of two people with an age difference of no more than 1 year is observed in early working ages (from 18 to 22 years). The introduced restrictions reduce the level of consumption by about a third at the age of 18-19 years. The introduced restrictions increase the average per capita level of consumption in the age group of 22-45 years by an average of 9.4% compared to classical calculations. The opposite situation is observed in the age group of 70-80 years old: the introduced restrictions reduce the average per capita level of consumption by 2.9%.Conclusion. The paper draws attention to the different results of the calculation of age consumption, depending on the methodological features. The author introduces the term “net age consumption”, which is calculated for households with an age difference between household members of no more than 1 year. Suggestions for estimating per capita consumption can be applied to model human consumption over the life cycle. At the same time, as a rule, the characteristics of households are far from the “model” consumption, which necessitates further study of the factors affecting the level of consumption depending on the characteristics of the household.